THEORETICAL QUESTIONS OF THE APPLIED ANALYSIS OF MORTALITY IN ROAD ACCIDENTS - Olga A. Mahova (Статистика и экономика)
The article outlines the need for the allocation of deaths due to road traffic accidents (RTA) as an independent object of study. Disclosure is necessary to estimate the mortality due to accidents and based global problem under consideration. An assessment of current trends in mortality in Russia because of the accident. Conclusions about the effectiveness of government policy in the field of road safety are formulated.